7y-6y+2y-8y-3y+y=

Simple and best practice solution for 7y-6y+2y-8y-3y+y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y-6y+2y-8y-3y+y= equation:


Simplifying
7y + -6y + 2y + -8y + -3y + y = 0

Combine like terms: 7y + -6y = 1y
1y + 2y + -8y + -3y + y = 0

Combine like terms: 1y + 2y = 3y
3y + -8y + -3y + y = 0

Combine like terms: 3y + -8y = -5y
-5y + -3y + y = 0

Combine like terms: -5y + -3y = -8y
-8y + y = 0

Combine like terms: -8y + y = -7y
-7y = 0

Solving
-7y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '-7'.
y = 0

Simplifying
y = 0

See similar equations:

| 0.3+0.75-6+3=x | | 4.2x-15.4=18.2 | | 6a+3a-7a= | | -15x-19=-94 | | 3x+-41=10 | | x+(x*.07)=40000 | | Y=33+-12x | | 4(n+6)=2n-9 | | 5h+17=2h+39 | | Y=4x-16x+33 | | 3.9(0.9x+7.34)=3.78x | | -6(x-1)17=-7x+2 | | 1/10(x-11)=-2(8-x) | | 10s+4n=84 | | 14x+25=73-2x | | (15/100)*x=50 | | 8x-2=12x-30 | | x^2+y^3-z^4=0 | | 9z+10=1-3(5-3) | | 1s=5s | | 3squared-(-5)= | | 9c=7c+8 | | 9x^2+4=(-12x) | | 15x-5+x=-47 | | 40=-10(1+a) | | 16+2(x+11)=36 | | (1/2^2x1/2x(1/2)^3= | | 15-4=3(5x-4) | | 18x+4y=162000 | | V=c-crt | | 15x+3=18x | | 3(2t+10)= |

Equations solver categories